Multicultural Education Based on Local Tradition of Selametan in History Learning Practice - Roro Wilis; Ajeng Diah Kinanti; Winda Pitriani Parhamah; Aldi Hendra Pratama (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
Radicalism remains a threat in Indonesia, where extreme views are rooted in a misguided understanding of diversity. History lessons at State Senior High School 9 in Yogyakarta adopt a multicultural education approach to promote understanding of diversity by introducing local Javanese traditions, such as selametan, through an inclusive model. This study explores how history education at State Senior High School 9 in Yogyakarta integrates the material taught with multicultural values to promote tolerance and inclusiveness. This study uses a qualitative case study method at SMA Negeri 9 Yogyakarta, with data collection techniques including observation, in-depth interviews, and document analysis. The sampling technique used is purposive sampling, involving several subjects, including the Deputy Principal for Curriculum, Deputy Principal for Facilities and Infrastructure, history teachers, and representatives of 10th grade students at SMA Negeri 9 Yogyakarta. Data validity and reliability were obtained through data triangulation techniques and analyzed using an interactive model. The research findings show that integrating history material with the local Javanese tradition of selametan is an effective way to foster tolerance and cooperation among students from diverse backgrounds. This strategy involves a collaborative Project-Based Learning (PjBL) model, demonstration methods, and class discussions to provide an understanding of diverse perspectives and encourage students to get used to living side by side. In this context, a school culture that accommodates student diversity also plays a crucial role in creating an inclusive and fair learning environment.